PANoptosis in Bacterial Infections: A Double-Edged Sword Balancing Host Immunity and Pathogenesis - Xiaoe He; Xiangyan Jiang; Jiayin Guo; Hui Sun; Jing Yang (Pathogens)
PANoptosis is a newly identified programmed cell death pathway that integrates characteristics of apoptosis, pyroptosis, and necroptosis. It plays a dual role in the host immune response to bacterial infections. On one hand, PANoptosis acts as a protective mechanism by inducing the death of infected cells to eliminate pathogens and releasing pro-inflammatory cytokines to amplify the immune response. On the other hand, bacteria can exploit PANoptosis to evade host immune defenses. This dual nature underscores the potential of PANoptosis as a target for developing novel therapies against bacterial infections. This review summarizes the molecular mechanisms of PANoptosis, along with the crosstalk and integration of different cell death pathways in response to various bacterial pathogens. We also discuss the dual roles of PANoptosis in bacterial infectious diseases, including sepsis, pulmonary infections, and intestinal infections. Elucidating the molecular mechanisms underlying PANoptosis and how bacteria manipulate this pathway offers critical insights into host–pathogen interactions. These insights provide a foundation for designing targeted antibacterial strategies, modulating inflammation, and advancing precision medicine to improve clinical outcomes.